Formação profissional e extensão em recreação hospitalar : o Projeto Sorria e a perspectiva de formação intercultural na educação física - Costa, Cleiton Jurandir da (2021)
This study aimed to understand the process of education of the body of Physical Education students within the extension project Recreation for young, adult, and elderly hospitalized patients (Sorria Project) at the Júlio Muller University Hospital. The problematization of the education in the hospital environment considered the experience of five Physical Education students who worked for at least a year as scholarship holders of the Sorria FEF/HUJM/UFMT extension project. The qualitative and explanatory research, carried out after the participation in the Sorria Project, resorts to the analysis of data collected with the participants of the formative process as extension scholarship holders, by means of semi-structured interviews, field notebook annotations, and the researcher's photographic record during his experience in the supervised internship of the Physical Education undergraduate course at UFMT in the hospital space. To apprehend the interviews, the technique of interpretive analysis and units of meaning was used, thus allowing an in-depth investigation of the interviewees' narratives. For the development and support of the investigation, we resorted to the conceptual understanding of recreation and its insertion in the hospital context from the literature and the theoreticalmethodological perspective of the Body, Education, and Culture Research Group, for the understanding of the education processes that are inscribed in the bodies mediated by cultures or intercultural educations potentiated in conflictive environments whose collectivity is established in the difference. The analysis of the documents potentiates the recognition of hospital recreation as a right to humanizing health of/in the body-patient and in the description of the formative process, which unveils the educative practices recreated as a potential of formation in the body-students. With the data analysis, we understand the importance of university extension in the academic, scientific and professional formation of Physical Education students; the proposal and the pedagogical activities that potentiated the formation in action of the students in the Sorria Project; the hospital context through recreation as a space for socialization and significant learning, promoting joy and will to live in affective and social interaction with the differences expressed in the bodies regarding body-students, body-patients, and body-technicians; and, finally, the studies developed in the formations of the Body, Education, and Culture Research Group, which led us to recognize the potential of intercultural education for the professional training of Physical Education teachers and educators. The interculturality that permeates the interviewees' narratives qualifies the hospital environment as a relevant space for the training of Physical Education professionals.